The effects of creatine pyruvate and creatine citrate on performance during high intensity exercise - Jäger, R.; Metzger, J.; Lautmann, K.; Shushakov, V.; Purpura, M.; Geiss, L. R.; Maassen, N. (Journal of the International Society of Sports Nutrition, 2008)
A double-blind, placebo-controlled, randomized study was performed to evaluate the effect of oral creatine pyruvate (Cr-Pyr) and creatine citrate (Cr-Cit) supplementation on exercise performance in healthy young athletes.